TINDAK TUTUR ILOKUSI DALAM IKLAN DI RRI SAMBAS 97.7 MHz - Permata, Indah; Muzammil, Ahmad Rabi’ul Muzammil; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to describe the types of illocutionary speech acts, illocutionary speech act functions, illocutionary speech act effects, and produce a form of Indonesian learning text supplement based on illocutionary speech acts in advertisements on RRI Sambas 97.7 MHz. The method used in this study is a qualitative descriptive method. The source of data in this study is recordings of public service advertisements broadcast through radio media that are suspected to have aspects of illocutionary speech acts. Data collection techniques are documentary study techniques, listen, record. Data validity testing techniques are Techniques to increase persistence and Triangulation techniques. This study produced representative illocutionary speech act types 7, directive 7, expressive 4, commissive 1. Assertive illocutionary speech act function 7, directive 8, expressive 3, commissive 1. Effects of illocutionary speech acts positive 13 and negative 6. The form of Indonesian learning text based on illocutionary speech acts in advertisements on RRI Sambas 97.7 MHz produces explanatory text.